Effects of supernova feedback on the formation of galaxy discs - Scannapieco, Cecilia (2008)
We use cosmological simulations in order to study the effects of supernova (SN) feedback on the formation of a Milky Way-type galaxy of virial mass ∼1012 h−1 M. We analyse a set of simulations run with the code described by Scannapieco et al., where we have tested our star formation and feedback prescription using isolated galaxy models. Here, we extend this work by simulating the formation of a galaxy in its proper cosmological framework, focusing on the ability of the model to form a disc-like structure in rotational support. We find that SN feedback plays a fundamental role in the evolution of the simulated galaxy, efficiently regulating the star-formation activity, pressurizing the gas and generating mass-loaded galactic winds. These processes affect several galactic properties such as final stellar mass, morphology, angular momentum, chemical properties, and final gas and baryon fractions. In particular, we find that our model is able to reproduce extended disc components with high specific angular momentum and a significant fraction of young stars. The galaxies are also found to have significant spheroids composed almost entirely of stars formed at early times. We find that most combinations of the input parameters yield disc-like components, although with different sizes and thicknesses, indicating that the code can form discs without fine-tuning the implemented physics. We also show how our model scales to smaller systems. By analysing simulations of virial masses 109 and 1010 h−1 M, we find that the smaller the galaxy, the stronger the SN feedback effects.